Using Efficient Contracting Theory To Find Out The Companies’earnings Quality (Vallis Aurea, 2024)
Profit is one of the information from financial statements that is still considered by investors or creditors. Therefore, accounting profits that have good quality are important information for potential investors and creditors in making the right decisions. Management has an information regarding the condition of the company and is likely to change or exaggerate the existing information, so efficient contract requests for financial accounting information is coming from lenders and shareholders. This study aims to examine the effect of leverage, outstanding shares, and good corporate governance on the earnings quality of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020. Leverage is measured by Debt to Asset Ratio (DAR), outstanding shares is measured by Cummulative Abnormal Return (CAR), good corporate governance is measured by the 1st level of ASEAN Corporate Governance Scorecard (ACGS), and earnings quality is measured by earnings quality ratio. The number of samples in this study were 104 companies that was taken by purposive sampling technique, tested using the multiple linear analysis method, and processed using SPSS Statistics 25 software. The results of this study show that outstanding shares have a positive effect on earnings quality, while leverage and good corporate governance have no effect on earnings quality.